Factors Contributing Students Motivation Toward English Language Learning (American International Journal of Humanities, Arts and Social Sciences, 2019)
The purpose of this research is to identify those factors that students are motivated toward English language learning. Furthermore, the study applied quantitative approach and the instrument was questionnaire to collect the data, and the questionnaire have been adopted, the software for analyzing the data were SPSS and calculated the percentage for the findings. Moreover, the major findings revealed as follow; first, English helps/will help me meet foreigners, second, English will be helpful for my career, third; English helps/will help me in my travel overseas and fourth; Studying English can be important for me because it will help me to further my studies.